Rule and Resistance Beyond the Nation State: Contestation, Escalation, Exit - Nicole Deitelhoff (Resistance Studies: Critical Engagements with Power and Social Change, 2019)
Rule and resistance can no longer be understood in national contexts only. They both have transnationalised over the last decades. The scholarly discourse, however, still lags behind these developments. While International Relations only sees institutional "governance", social movement studies only see instances of resistance. Both, however, lack the necessary vocabulary to describe the dynamic interplay between systems of rule and resistance. While we are governed by transnational structures of rule, a systematic analysis of how this operates and how it can be resisted remains to be developed. This book develops an understanding of these power relations through rich empirical case studies of different forms of rule-resistance relationships. Some resistant groups demand reforms of particular policies and institutions. Others attack institutions head-on. Yet other actors attempt to escape the rules they reject. Which forms of resistance can we expect under different kinds of rule? How can we understand transnational rule in the first place? The book gives new inspiring answers to these difficult questions.